Tutors Effective Teaching and Students Pass Rates in Teacher Colleges in Tanzania (Global Journal of Human-Social Science, 2017)
Scholars and education practitioners agree that a teacher tutor is an important factor in education and training Teachers organize and guide students in their learning experience and interaction with the content of the curriculum and at all times promote students initiatives and readiness for their own learning Nuthall 2004 Multiple group and different people in the society react in a different way from what is happening in Teacher Colleges Sometimes Tutors are blamed for poor performance of students in national examinations In this paper two objectives guide the study to find out the relationship between interaction styles and students examination pass rates and to establish the relationship between instructional procedures and students examination pass rates The data for this paper were collected in 2013 through questionnaire survey The samples of the participants were 120 tutors from Mpwapwa and Morogoro Teacher Colleges respectively Pearson Correlation Coefficient was used to measure the strength and direction between the correlated variables Statistical tests were used at a two-tailed test of significance at P 0 05 probability level of confidence The finding here are part of Master Dissertation on Tutor effective teaching and students examination pass rates in Teacher Colleges in Tanzania
Keywords: effective teaching; examination pass rates; teacher colleges; instructional procedures; interaction styles